Evaluation of two rapid antigen assays, BioStar Strep A OIA and Pacific Biotech CARDS O.S., and culture for detection of group A streptococci in throat swabs. - Dale, J C (1994)
Two rapid methods, BioStar Strep A OIA (OIA; BioStar, Inc., Boulder, Colo.), an optical immunoassay, and CARDS O.S. (O.S.; Pacific Biotech, Inc., San Diego, Calif.), a color immunochromographic assay, and two culture methods, one with 5% sheep blood agar (SBA) and one with Todd-Hewitt broth (TH; Remel, Lenexa, Kans.), were evaluated for use in the detection of Streptococcus pyogenes from pharnygeal swabs. Seven hundred forty-six double swabs (Culturette II) were processed, with OIA and SBA culture performed on one swab and O.S. and SBA culture performed on the other swab. The pledget from the Culturette II was incubated overnight in TH and was subcultured onto SBA for an additional 48 h in ambient air. All beta-hemolytic streptococci from culture were tested by a direct fluorescent-antibody test (Difco Laboratories, Detroit, Mich.). Specimens with discordant fluorescent-antibody test and rapid test results were also tested by using the Streptex latex agglutination reagent (Murex Diagnostics Limited, Dartford, England). The results obtained by all testing methods were compared with a combined test result ("gold standard"), which was defined as any positive culture detected by the SBA or TH culture methods and confirmed by Streptex latex agglutination or, in the case of negative results by both culture methods, a concomitant positive result by OIA and O.S. antigen testing. Sensitivity and specificity results for each of the methods were as follows, respectively: OIA, 81.0 and 97.5%; O.S., 74.4 and 99.0%; SBA culture, 92.3 and 98.3%; and TH culture, 86.4 and 100%. Both OIA and O.S. are suitable screening methods for detecting S. pyogenes directly from throat swabs but are of insufficient sensitivity to eliminate the need for backup cultures for specimens with negative OIA and O.S. results.